Midwifery Care for Pregnant Women Mrs. R with Preeclampsia at Veronica Clinic, Stabat Lama Village, 2019 - Ernita Ruslaini Caniago; Setia Sihombing; Siti Nurhaliza; Melda Gunawan (Science Midwifery, 2019)
The results of the 2012 Indonesian Demographic and Health Survey (IDHS) stated that the MMR in Indonesia was 359 per 100,000 KH. According to the Indonesian Health Profile, the highest causes of maternal mortality in 2013 were bleeding, Hypertension in Pregnancy (HDK), infection, prolonged/obstructed labor and abortion. Mothers who experience hypertension due to pregnancy range from 10%, 3.4% of them have pre-eclampsia, 5% have hypertension and 1-2% have chronic hypertension. Type of case study report with descriptive method, location at BPS Deniawati Kwala Bingai Stabat. Data collection techniques include primary data including physical examination, interviews and observation and secondary data, including documentation studies and literature studies. Able to carry out midwifery care for pregnant women with mild pre-eclampsia using Varney's 7-step midwifery approach. Results For midwifery care for pregnant women at BPS Rusnah after carrying out midwifery care for 3 weeks the results were: Blood pressure 150/90 mmHg, to 120/80 mmHg, Urine protein from (+1) to (-). Although in this case there is a gap between theory and practice, the midwife can provide care to the patient so that a potential diagnosis in the form of severe pre-eclampsia does not occur. The results of midwifery care carried out for 3 weeks were the mother did not feel dizzy anymore, blood pressure became 120/80 mmHg, urine protein (-) and there was no edema in the left and right legs (pregnant women did not experience pre-eclampsia anymore).